The perception of students about the effect of electronic device use on sleep quality (Research, Society and Development, 2025)
Introduction: Sleep is essential for physical and mental health, influencing quality of life. Excessive use of electronic devices at night is a major factor impairing sleep quality. Higher education students are a vulnerable group with a high prevalence of sleep disorders. Objective: To analyze students' opinions on the interference of electronic device use on sleep quality. Methods: This opinion study, based on Resolution No. 510/2016, was conducted through an online questionnaire distributed via digital platforms. The sample consisted of higher education students, and data were collected over 30 days. Responses were organized in spreadsheets and analyzed descriptively. Results: Ninety-nine percent of participants believe that electronic device use harms sleep onset. About 95% use their phones after going to bed, and 96% reported sleeping later than intended due to digital distraction. Phones were identified by 90% as the main factor related to nighttime awakenings. However, 64% do not consider sleep medication necessary, attributing sleep disturbances to behavioral habits. Additionally, 100% believe students spend more time than ideal in front of screens. Conclusion: The data reveal a significant perception among students of the negative impact of electronic device use on sleep quality. Despite awareness, nighttime behaviors remain inadequate, highlighting the need for educational strategies and institutional actions.